Marcadores tumorales séricos, como ayuda diagnóstica en el cáncer de mama - Cambal Vilema, Slendy Paola (2023)
ABSTRACT: Breast cancer is a pathology with a higher prevalence in women. According to the World Health Organization (WHO), Cancer is the leading cause of death in this population, which is why it is necessary to have laboratory parameters and tests that help in the diagnosis. , assessment, prediction, and control of this condition. Tumor biomarkers are substances detectable in biological fluids and other body tissues. The objective of this study was to investigate the serum tumor markers most used for the diagnosis of breast cancer, analyzing the methods, prevalence, and predisposing factors. The research is documentary, non-experimental, cross-sectional, and retrospective from different scientific databases such as Scopus, Google Scholar, PubMed, ProQuest, Cochrane, and SciELO. The most significant data after the discussion of several authors establishes that carbohydrate antigen 15-3 (CA 15-3) and carcinoembryonic antigen (CEA) are used in the pre-diagnostic evolution after treatment of this Cancer. Due to its high sensitivity and specificity, the analysis method used in the laboratory is the electrochemiluminescence immunoassay (ECLIA). Still, the Ezymoimmunoassay adsorption assay (ELISA) is commonly chosen due to its accessibility. It was evident that the prevalence of this Cancer is found primarily in metastatic patients compared to an average person, detected using the CEA marker, and the risk factors have not yet been precisely established; however, age, early menarche, family history, among others, enable its development.